An unusual case of mesenteric ischaemia. Issue 1 (18th September 2013) - Ayres, L R O; Scott, M; Shepherd, N; Brown, J
Abstract : We describe an unusual cause of diarrhoea and segmental colitis in a previous well adult man. Mesenteric inflammatory veno-occlusive disease is a rare cause of gastrointestinal tract ischaemia of unknown aetiology. We review the literature of this condition and other mesenteric venous pathologies.